Healthier haulage - Thompson, Roger (Mining Magazine, 2011)
Research at Curtin University Western Australian School of Mines embodies considerable accumulated practical mine road-design knowledge, both through applied research in mine haul road design and construction, and through various road design, construction and rehabilitation case studies both locally and internationally. One of the most common issues encountered in mine road-based haulage is to predict and accommodate changes in haul road performance – or ‘trafficability’, both from the design and safety perspectives. How well equipped a mine is to deal with the issue is related to how robust its road-design and -safety management systems are.